1980
DOI: 10.3102/00346543050002343
|View full text |Cite
|
Sign up to set email alerts
|

The Measurement and Treatment of Test Anxiety

Abstract: A review of the literature concerning the self-report test anxiety scales and treatment of test anxiety was conducted. The various popular self report test anxiety instruments were examined with attention given to the reliability and validity status of the scales. Treatment studies were reviewed, with attention being paid to both the outcomes presented and the designs used. Treatments directed toward test worry were more effective in reducing self reported test anxiety and increasing grades than treatments dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0
1

Year Published

1981
1981
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(51 citation statements)
references
References 125 publications
2
48
0
1
Order By: Relevance
“…A score ≤ 12 is considered as mild test anxiety, a score of 12 -20 is considered as moderate test anxiety, and a score > 20 is considered as sever test anxiety (22). Troyn (1980) reported the reliability of the scale 0.80 by test-retest reliability and by the split-half method reported it as 0.91 (23). In the study by Yazdani (2012), Cronbach's alpha coefficient of the questionnaire was reported 0.88, internal consistency was reported 0.95, and standard validity was reported 0.72 (24).…”
Section: Study Population and Samplingmentioning
confidence: 99%
“…A score ≤ 12 is considered as mild test anxiety, a score of 12 -20 is considered as moderate test anxiety, and a score > 20 is considered as sever test anxiety (22). Troyn (1980) reported the reliability of the scale 0.80 by test-retest reliability and by the split-half method reported it as 0.91 (23). In the study by Yazdani (2012), Cronbach's alpha coefficient of the questionnaire was reported 0.88, internal consistency was reported 0.95, and standard validity was reported 0.72 (24).…”
Section: Study Population and Samplingmentioning
confidence: 99%
“…Nevertheless, emotionality is the learner's subjective consciousness of the intensified autonomic arousal rather than the arousal itself (Schwarzer, 1984). Different studies revealed that worry has a stronger association with performance than emotionality (Deffenbacher, 1980., Goonan, 2003., Tryon, 1980. Three models describe the causes of test anxiety.…”
Section: Test Anxietymentioning
confidence: 99%
“…A furtherpossibility is that test anxietyand test performance each affect one another, i.e., the causal relationship is bidirectional (e.g., Hill, 1972). Another viewthat appears to be gaining support is that test anxiety is simply a natural reaction to poortest-taking skills (Tryon, 1980), with the inabilityto process information as likely to elicitanxietyas anxietyis to impair information processing (Benjamin, McKeachie, Lin, & Holinger, 1981;McKeachie, 1984;PauIman& Kennelly, 1984). Any debilitating effects of test anxiety may depend on a varietyof other factors, such as test takers' information organizing skills (Birenbaum & Pinku, 1997) and, we hypothesize, their anxietyabout computers.…”
Section: Significance Of the Problemmentioning
confidence: 99%